The effect of heat treatment on mechanical properties for ductile cast iron parts welded by (Inconel 625) electrodes (Journal of Hama University, 2019)
This research includes the study of samples of ductile cast iron, they were analyzed chemically and determine their mechanical properties, and then weld it by arc electric welding using (Inconel 625) welding electrodes type. In two cases, the first one is pre-heating of the samples was carried out to a temperature of 500 c and the second was weld directly, and then we made heat treatment on all samples (tempering at 400 c for a number of samples and annealing at 650 c for the other samples). The effect of preheating and subsequent heat treatment on the mechanical properties of the welded parts was studied. The results showed a decrease in hardness and The tensile strength of pre-preheating and subsequent heat treatments samples, as well as the rise in impact resistance, that is because  during the tempering, the hardness of the martensite is reduced as the unstable crystalline structures (martensite) formed after the cooling process returned to a more stable position, where the martensite breaks down into ferrites and carbides. The transformation speed is small at low temperatures because the movement of carbon inside martensite requires temperature and time. The annealing process, allowing the carbon to be redistributed within the structure. As a result of the annealing process, crystallization of the granules takes place, thus obtaining a homogeneous pearlite structure with soft granules. This is the main reason for the low hardness and tensile strength and high toughness.